Barriers to telephone cardiopulmonary resuscitation in public and residential locations. (December 2016) - Fukushima, Hidetada; Panczyk, Micah; Spaite, Daniel W.; Chikani, Vatsal; Dameff, Christian; Hu, Chengcheng; Birkenes, Tonje S.; Myklebust, Helge; Sutter, John; Langlais, Blake; Wu, Zhixin; Bobrow, Bentley J.
Abstract: Aim: Emergency medical telecommunicators can play a key role in improving outcomes from out-of-hospital cardiac arrest (OHCA) by providing instructions for cardiopulmonary resuscitation (CPR) to callers. Telecommunicators, however, frequently encounter barriers that obstruct the Telephone CPR (TCPR) process. The nature and frequency of these barriers in public and residential locations have not been well investigated. The aim of this study is to identify the barriers to TCPR in public and residential locations. Methods: We conducted a retrospective study of audio recordings of EMS-confirmed OHCAs from eight regional 9-1-1 dispatch centers between January 2012 and December 2013. Results: We reviewed 1850 eligible cases (public location OHCAs: N = 223 and residential location OHCAs: N = 1627). Telecommunicators less frequently encountered barriers such as inability to calm callers in public than in residential locations (2.1% vs 8.5%, p = 0.002) or inability to place victims on a hard flat surface (13.9% vs 25.4%, p < 0.001). However, the barrier where callers were not with patients was more frequently observed in public than in residential locations (11.8% vs 2.7%, p < 0.001). Conclusions: This study revealed that barriers to TCPR are distributed differently across public and residential locations. Understanding these differences can aid in the development of strategies to enhance bystander CPR and improve overall patient outcomes.